2021
DOI: 10.3390/su13179712
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Based Classification and Regression Approach for Sustainable Disaster Management: The Case Study of APR1400 in Korea

Abstract: During nuclear accidents, decision-makers need to handle considerable data to take appropriate protective actions to protect people and the environment from radioactive material release. In such scenarios, machine learning can be an essential tool in facilitating the protection action decisions that will be made by decision-makers. By feeding machines software with big data to analyze and identify nuclear accident behavior, types, and the concentrations of released radioactive materials can be predicted, thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The research demonstrated that offsite parameters could support prompt decisionmaking during a nuclear disaster when onsite parameters are unavailable [1]. In this case, machine learning is a viable option for the underlying assessments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The research demonstrated that offsite parameters could support prompt decisionmaking during a nuclear disaster when onsite parameters are unavailable [1]. In this case, machine learning is a viable option for the underlying assessments.…”
Section: Discussionmentioning
confidence: 99%
“…The receiver operator characteristic (ROC) curve with its area under the curve (AUC) is another metric for evaluating the four models' performance in correctly classifying each accident. ROC AUC is the probability that the classification model ranks a random positive for a specific accident [1]. Generally, the classification of the four models for each accident type was excellent and never went below 0.97.…”
Section: Roc Aucmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies highlight the usefulness of technologies for EDMPP. To focus on a few technologies; various studies describe the utility of artificial intelligence and machine learning and reasoning [69,71,80,168,169,[193][194][195][196][197][198][199][200][201][202][203][204][205][206][207][208][209][210] for EDMPP including for the evaluation of societal implications [211]. If it is seen as useful to evaluate societal implications, the data must contain high quality information on the 'social', especially in relation to marginalized groups.…”
Section: Edmpp Marginalized Groups Edi and Technologymentioning
confidence: 99%
“…ML models have also been used to predict the difusion and transport of radioactive materials in the atmosphere [17,18] and the prediction of the radioprotector compounds' efectiveness and toxicity [19]. Furthermore, IAEA is supporting the increasing trend of using robots in environments contaminated with radiation [20].…”
Section: Introductionmentioning
confidence: 99%